2009
DOI: 10.1002/bjs.6434
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing decellularized bovine ureter with expanded polytetrafluoroethylene for vascular access

Abstract: Both grafts were adequate conduits for haemodialysis and were amenable to repair. Anticipated advantages for SG 100 were not seen in either patency or stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 22 publications
(15 reference statements)
0
53
0
Order By: Relevance
“…2; [16]). There was little evidence of cellular residue on the surfaces of the matrices in groups IV and V, however, a small amount of cell residue was visible on the surfaces of the scaffolds in groups I, II and III.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2; [16]). There was little evidence of cellular residue on the surfaces of the matrices in groups IV and V, however, a small amount of cell residue was visible on the surfaces of the scaffolds in groups I, II and III.…”
Section: Resultsmentioning
confidence: 99%
“…In the experimental groups, infiltrations of host cells into the grafts were observed (Fig. 3; [26]). Especially for groups II and V, the host cell infiltration was less.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 On the other hand, Chemla et al found that both grafts were adequate conduits for HD, the anticipated advantages for SG 100 were not seen in either patency or stability. 41 …”
Section: Biological Conduits For Hemodialysismentioning
confidence: 99%